The Role of Autophagy in Acute Myocardial Infarction - Wu, Du; Zhang, Kangfeng; Hu, Pengfei (Frontiers in Pharmacology, 2019)
Acute myocardial infarction refers to a sudden death of cardiomyocytes, which leads to a large mortality worldwide. To attenuate acute myocardial infarction, strategies should be made to increase cardiomyocyte survival, improve postinfarcted cardiac function as well as reversing the process of cardiac remodeling. Autophagy, a pivotal cellular response, has been widely studied to be involved in various kinds of diseases. In the recent few years, the role of autophagy in diseases has been drawn increasing attention to by researchers. Here in this review, we mainly focus on the discussion of the effect of autophagy on the pathogenesis and progression of acute myocardial infarction under ischemic and ischemia/reperfusion injuries. Furthermore, several popular therapeutic agents and strategies taking advantage of autophagy will be described.